Thermoelectric properties of SnSe2 monolayer. (10th November 2016) - Li, Guanpeng; Ding, Guangqian; Gao, Guoying
Abstract: The 2H (MoS2 -type) phase of 2D transition metal dichalcogenides (TMDCs) has been extensively studied and exhibits excellent electronic and optoelectronic properties, but the high phonon thermal conductivity is detrimental to the thermoelectric performances. Here, we use first-principles methods combined with Boltzmann transport theory to calculate the electronic and phononic transport properties of 1T (CdI2 -type) SnSe2 monolayer, a recently realized 2D metal dichalcogenide semiconductor. The calculated band gap is 0.85 eV, which is a little larger than the bulk value. Lower phonon thermal conductivity and higher power factor are obtained in 1T-SnSe2 monolayer compared to 2H-TMDCs monolayers. The low phonon thermal conductivity (3.27 W mK −1 at room temperature) is mainly due to the low phonon frequency of acoustic modes and the coupling of acoustic modes with optical modes. We also find that the p -type has better thermoelectric performance than the n -type, and the figure of merit within p -type can reach 0.94 at 600 K for 1T-SnSe2 monolayer, which is higher than those of most 2H-TMDCs monolayers, making 1T-SnSe2 monolayer a promising candidate for thermoelectric applications.